Clnk, a Novel Slp-76–Related Adaptor Molecule Expressed in Cytokine-Stimulated Hemopoietic Cells - Cao, Ming Yu (The Rockefeller University Press, 1999)
We have identified a novel Src homology 2 domain–containing leukocyte protein of 76 kD (SLP-76)–related molecule which we have termed Clnk (for cytokine-dependent hemopoietic cell linker). Unlike its relatives SLP-76 and B cell linker protein (Blnk), Clnk is not expressed uniformly within a given hemopoietic cell lineage. Even though it can be detected in several cell types, including T cells, natural killer cells, and mast cells, its expression seems to be strictly dependent on sustained exposure to cytokines such as interleukin (IL)-2 and IL-3. Strong support for the notion that Clnk is involved in immunoreceptor signaling was provided by the observation that it inducibly associated with at least one tyrosine-phosphorylated polypeptide (p92) in response to immunoreceptor stimulation. Moreover, transient expression of Clnk caused an increase in immunoreceptor-mediated signaling events in a T cell line. Taken together, these results show that Clnk is a novel member of the SLP-76 family selectively expressed in cytokine-stimulated hemopoietic cells. Furthermore, they suggest that Clnk may be involved in a cross-talk mechanism between cytokine receptor and immunoreceptor signaling.